Implementasi Pengembangan Kurikulum 2013 dalam Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMA Negeri 4 Jember: Implementation of the 2013 Curriculum Development in Islamic Religious Education and Character Learning at SMA Negeri 4 Jember - Hj. Titek Rohanah Hidayati (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2015)
This study aims to examine the implementation of the 2013 Curriculum development in Islamic Religious Education and Character learning at SMAN 4 Jember, which includes: (1) Planning of Islamic Religious Education and Character learning under the 2013 Curriculum at SMA Negeri 4 Jember, (2) Implementation of Islamic Religious Education and Character learning under the 2013 Curriculum at SMA Negeri 4 Jember, and (3) Evaluation of Islamic Religious Education and Character learning under the 2013 Curriculum at SMA Negeri 4 Jember. This research uses a qualitative approach. The conclusions of this study are: first, the implementation of planning for Islamic Religious Education and Character learning under the 2013 Curriculum includes annual programs, semester programs, weekly and daily programs, as well as remedial and enrichment programs. Second, the implementation of Islamic Religious Education and Character learning under the 2013 Curriculum involves fostering closeness and pre-tests, competency formation, and post-tests. Third, the evaluation of Islamic Religious Education and Character learning under the 2013 Curriculum includes assessments of attitude competencies, knowledge competencies, and skill competencies. However, overall, the development of the 2013 Curriculum in Islamic Religious Education and Character learning at SMAN 4 Jember is considered maximal in terms of planning and implementation, but the assessment system still needs improvement. Penelitian ini bertujuan untuk mengkaji implementasi pengembangan Kurikulum 2013 dalam pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMAN 4 Jember yang meliputi: Perencanaan Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Pada Kurikulum 2013 di SMA Negeri 4 Jember. Pelaksanaan Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Pada Kurikulum 2013 di SMA Negeri 4 Jember. Evaluasi Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Pada Kurikulum 2013 di SMA Negeri 4 Jember. Penelitian ini menggunakan penelitian kualitatif. Kesimpulan penelitian ini adalah pertama, implementasi perencanaan pembelajaran Pendidikan Agama Islam dan Budi Pekerti pada kurikulum 2013 meliputi program tahunan, program semester, program mingguan dan harian, program remedial dan pengayaan. Kedua, implementasi pelaksanaan pembelajaran Pendidikan Agama Islam dan Budi Pekerti pada Kurikulum 2013 meliputi pembinaan keakraban dan pre test, pembentukan kompetensi, dan post test. Ketiga, implementasi evaluasi pembelajaran Pendidikan Agama Islam dan Budi Pekerti pada Kurikulum 2013 meliputi penilaian kompetensi sikap, penilaian kompetensi pengetahuan, dan penilaian keterampilan. Namun secara umum pengembangan Kurikulum 2013 pada pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMAN 4 Jember dipandang dari sistem perencanaan, pelaksanaan sudah maksimal namun pada sistem penilaian masih kurang maksimal.